Pengetahuan Ibu Hamil Tentang Pelaksanaan Senam Hamil - Miftahul Hakiki; Nurul Eko Widiyastuti (Citra Delima Scientific journal of Citra Internasional Institute, 2023)
Knowledge is the result of knowing, which is the result of people who have evaluated certain objects. Pregnancy exercise is a form of education that aims to maintain the elasticity of the abdominal muscles, ligaments or pelvic floor muscles which will later affect the delivery procedure. The purpose of this study, to find out whether there is a relationship between the knowledge of pregnant women about the implementation of pregnancy exercise. This type of research is descriptive correlational with a cross sectional approach. The population taken is all pregnant women. The samples taken were 45 respondents. Sampling using Purposive Sampling technique. Data collection using a questionnaire. Analysis using the Chi Square Test. The results of the analysis show that the value of Asymp Sig. (2-sided) 0.936 so that it can be categorized as having a very strong correlation. The higher the knowledge score of pregnant women regarding pregnancy exercise, the higher the score for carrying out pregnancy exercise, which affects the routine of pregnant women in carrying out pregnancy exercise. The conclusion is that there is a very strong correlation between the knowledge of pregnant women and the implementation of pregnancy exercise, the conditions in the field are that many pregnant women carry out pregnancy exercise. It can be suggested to pregnant women to continue to carry out pregnancy exercises during pregnancy so that they can prepare themselves for the delivery process.